Developing Students’ Speaking Skill Through Digital Storytelling - Amrul Hidayat; Sri Wahyuni Thamrin; Andi Anugrah M; St. Wahidah Z (JLE: Journal of Literate of English Education Study Program, 2024)
Students’ speaking ability of the eleventh grade at Pondok Pesantren Abu Bakar Ash-Shidiq was still classified as low. Therefore, it is necessary for the researcher to conduct the research in order to give significance theortically and practically. Theoretically, the result of this study was expected to support or refine the theory of EFL and ESL teaching. And, practically it is essential for those English teachers in designing a classroom activity to help the learners speak in English more accurately and fluently. This research aimed at finding out the improvement of the students’ speaking skills by using Digital Storytelling at the Eleventh Grade of Pondok Pesantren Abu Bakar Ash-Shidiq Taccorong. This research used pre-experimental method with 15 students of the eleventh grade of Pondok Pesantren Abu Bakar Ash-Shidiq Taccorong as the sample which was taken purposively from 32 as the population. The research findings showed that the mean score the value of post-test is higher than the pre-test’s value; 70,6>50,6. Furthermore, the t-test value of each speaking aspect and combination of aspects found were all higher than the t-table; 5.69>2.145, 4,65>2.145, and 11,8 > 2.145. The statistical research result indicates that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, it can be concluded that digital storytelling improved the students’ speaking ability